A sensitive fluorescence-visualized sensor based on an InP/ZnS quantum dots-sodium rhodizonate system for monitoring fish freshness. (1st August 2022) - Zhang, Jiaran; Wang, Yizhong; Xu, Zeyu; Shi, Ce; Yang, Xinting
Highlights: MPA-InP/ZnS QDs and sodium rhodizonate were used to construct an amines sensor. The sensor responds to amines by fluorescence and color change under UV light. Detection mechanism was based on the inner filter effect and static quenching effect. The sensitivity and detection range of the sensor can be flexibly adjusted. Selectively and rapid determination of fish freshness. Abstract: A fluorescence-visualized sensor based on 3-mercaptopropionic acid (MPA)-capped indium phosphide/ zinc sulfide quantum dots (InP/ZnS QDs) and sodium rhodizonate (SR) was designed to sensitively monitor fish freshness. MPA-InP/ZnS QDs, which exhibit orange-red fluorescence, were synthesized by a solvothermal method. In the MPA-InP/ZnS QDs-SR system, the fluorescence of MPA-InP/ZnS QDs was quenched by SR due to the combined function of the inner filter effect (IFE) and static quenching effect (SQE) at pH = 3. When ammonia was added, the fluorescence was recovered, and the color changed from colorless to bright orange-red under UV light (365 nm). The sensing performance for volatile amine gas was studied, and the sensor demonstrated good linearity between the fluorescence intensity, the total volatile basic nitrogen (TVB-N) and the total color change (ΔE) of bighead carp stored at room temperature (25 °C) and refrigerated temperature (4 °C). The proposed sensor has potential applications in monitoring fish freshness.